HEALTH LITERACY AND THE USES OF COMPLEMENTARY AND ALTERNATIVE MEDICINES AMONG PATIENTS WITH NON-COMMUNICABLE DISEASES - Thanapancharoen, Chutima; T.Sriwong , Burin; Bunchuailua, Waranee (Thai Bulletin of Pharmaceutical Sciences, 2025)
This study examined the association between health literacy (being able to access, understand, and make decisions using information related to health care) and the use of some complementary and alternative medicines (CAM) among patients with chronic non-communicable diseases (NCDs). A cross-sectional study was conducted among 261 patients receiving care at Nakhon Chai Si District Hospital, Nakhon Pathom Province, Thailand. Questionnaires were used during structured interviews from which the data was collected and analyzed using descriptive statistics and logistic regression. The findings revealed that the majority of patients with NCDs were female (61.7%) whose mean age was 56.3 ± 0.9 years. The most common comorbidities were hyperlipidemia, hypertension, and diabetes. Overall, 65.9% of the participants demonstrated an insufficient understanding of health literacy. Most patients (82.4%) reported using at least one type of CAM, with 48.2% using dietary supplements and 22.7% using herbal medicines. CAM was primarily used for disease management (43.4%), but was discontinued by 45.4% of the users due to adverse effects. Health literacy (OR=4.4, 95% CI 1.1-18.1, p=0.04) and education levels (OR=5.6, 95% CI 1.1-27.9, p=0.04) were significantly associated with CAM use. In conclusion, health literacy is a critical skill that enables NCD patients to make informed decisions in managing their illnesses and with using CAM appropriately. Therefore, enhancing health literacy is essential for ensuring effective, safe, and satisfactory patient care.